Emergency red cells first: Rapid response or speed bump? The evolution of a massive transfusion protocol for trauma in a single UK centre. Issue 9 (September 2015) - Boutefnouchet, Tarek; Gregg, Richard; Tidman, Jane; Isaac, John; Doughty, Heidi
Abstract Background Death from massive haemorrhage due to traumatic injury is potentially preventable after hospital admission using haemorrhage control and improved resuscitation techniques including massive transfusion protocols. Massive transfusion protocols (MTP) are an essential element of damage control resuscitation and provide a coordinated clinical pathology response to massive haemorrhage after hospital admission. The decision to activate and de-activate a MTP is based on a number of patient and local factors. The purpose of this before-and-after study was to determine the impact of modifying a protocol to include emergency red cells. In addition, we investigated whether massive transfusion prediction models could have been used to guide on-going transfusion support. Methods Sequential MTP activations over three years, before and after protocol revision, were analysed. Percentage of MTP activation, component usage and outcome data were compared. Trauma associated severe haemorrhage (TASH) and assessment of blood consumption (ABC) scores were derived and receiver operating characteristic (ROC) analysis undertaken for an outcome defined as the use of >6 red cell units. Results 52 MTP1 and 66 MTP2 activations arose from 216 and 495 major trauma cases, respectively. Protocol change significantly reduced the MTP activation rate (p = 0.0006) from 24% to 13%, and the number of activations requiring >10 RCC increased from 13% to 36% (p = 0.006). Average emergency red cells usage in the second cohort increased to 4 units. Survival, coagulation parameters, and time to MTP pack issue were all unaffected by the protocol revision. The TASH score showed an area under ROC (AUROC) of 0.88 ongoing transfusion requirements. Conclusion The change in protocol increased the use of emergency red cells but reduced MTP activation and use of multiple blood components. The TASH score appears to provide a useful predictive tool for ongoing transfusion support and may be of value for the trauma clinicians.